Avaliação da espessura cortical e volume de estruturas subcorticais associados ao fator neurotrófico derivado do cérebro (BDNF) em uma coorte de alto risco de desenvolvimento de transtornos psiquiátricos durante a infância e adolescência - Araujo, Celia Maria De [UNIFESP] (2018)
Background: The Brain Derived Neurotrophic Factor (BDNF) is a neurotrophin that plays a key role in synaptic plasticity and transmission. The BDNF Val66Met polymorphism (rs6265) has been associated with neuropsychiatric disorders and brain structural alterations in adults, but little is known about the effect of Val66Met on brain structure during typical or atypical neurodevelopment. Windows of vulnerability for psychopathology may be associated with both Val and Met BDNF alleles. Objective: This thesis aimed to investigate the effect of BDNF (genotype and serum) on cortical volume and thickness and on the volume of hippocampus and amygdala of healthy children and adolescents and in those at high risk of developing psychiatric disorder. Methodology: we conducted two studies that used the database of images and genetic data from 749 children and adolescents at high risk for the development of psychiatric disorders. They were participants of the cohort study that was conducted in Brazilian schools in 2010 (Highrisk cohort HRC). The first study investigated the effect of Val66Met on cortical thickness on MRI scans of 718 children and adolescents with typical and atypical development (according to the DAWBA criteria). The second study tested possible replicable correlations between BDNF peripheral concentrations, brain structure and psychopathology; and whether there was an effect of the BDNF genotype on the BDNF serum concentrations in late childhood and early adolescence. Results: The first study showed that typical developed Met carriers had thicker parietal/occipital lobes and prefrontal cortices compared to the homozygotes Val. In the group with some psychiatric diagnosis, it was observed that Met carriers had increased thickness of the temporal and lateral temporal cortices. In addition, a significant interaction between genotype x the psychiatric diagnosis was found with the Met allele carriers presenting thinner bilateral prefrontal cortices compared to the Val homozygotes.The results of the second study showed (in the two samples evaluated), lack of evidence to support any association between serum BDNF concentrations and cortical and subcortical volumes. Analyzes of interactions between Val66Met and sex or Val66Met and psychiatric diagnoses did not detect any effect on serum BDNF values in children with typical or atypical development. Conclusion: Children and adolescents (Met carriers) showed differences in cortical thickness of varying regions of the brain when compared to Val homozygotes. In addition, the affected brain regions were different between individuals with typical and atypical development. There was no association between serum concentrations of BDNF and cortical and subcortical volumes. These results suggest that the BDNF genotype may be associated with cerebral cortex maturation and play a key role in Gene X Environment interaction during developmental trajectories, which may contribute to understanding the pathophysiological mechanisms of earlyonset psychiatric disorders.